Positive Ageing Dalam Serial HULU: "Only Murder in The Building" - Muhammad Kafi Putra Jauhari (Jurnal Ilmu Komunikasi, 2022)
The representation of the older people in the media has become a popular research for the last ten years. In their presence in media such as television, advertisements, and films, parents have two characteristics, namely positive and negative. Parents in the media are usually presented in two very contradictory forms.One of these forms is that of an elderly person who is weak, dependent, and experiencing signs of aging. Meanwhile, the other form represents parents who are agile and independent, as well as fighting the signs of aging. There are differences in the representation of parents in the media on television and drama. In dramas, positive aging has a contribution in changing cultural norms and values of aging. This studyuses a semiotic analysis descriptive approach which is a method in analyzing a study to examine signs. The signs in question are elements in looking for something on a particular object. In semiotic analysis it will help researchers to identify various signs in communication. Semiotic analysis is used to interpret artificial signs based on the researcher's rational logic. So that from these different thoughts gave birth to several schools of semiotics, namely semiotics of structuralism, pragmatism, and postmodernism.